Perbedaan Hasil Pemeriksaan LED Secara Manual dan Menggunakan Alat Automatic - Arip Wahyudi; Maria Nuraeni; Margareta Haiti (Jurnal Laboratorium Prima, 2023)
In 1973 it was stated and published that the Westergren method was the method recommended by the ICSH (International Committee for Standardization in Hematology). The manual LED examination of the Westergren method was carried out on blood samples with EDTA anticoagulant and took 60 minutes, but now an LED examination with One of the automatic methods is using the HumaSRate tool. The HumaSRate tool only takes 20 minutes to examine samples. In this study the researchers examined the differences in LED inspection results manually and using automatic tools. The results of this study found that there were no differences in LED inspection results between methods manual and automatic. Know the differences in LED Inspection Results Manually and Using Automatic Tools This research is an analytic observation with a cross sectional approach using total sampling technique. The research subjects were 33 students who met the inclusion and exclusion criteria. The results of LED inspection using manual and automatic methods were tested using the Wilcoxon test. The average manual method of LED inspection is 18.5 mm/hour. The average LED inspection by the automatic method is 19.0 mm/hour with a statistical test result of p-value = 0.167 (> 0.05). There is no difference in the results of the LED inspection between the manual and automatic methods. For future researchers, if they want to conduct research similar to this study, it is advisable to conduct research using two different automatic tools and with different sample processing times.